Análise de parâmetros neuromusculares e cinemáticos dos chutes Bandal Chagui e Dolhô Chagui do Taekwondo - Moreira, Pedro Vieira Sarmet [UNESP] (2015)
Abstract The purpose of this study was to compare kinematic and neuromuscular parameters of roundhouse (RK) kick in athletes of two different standards. 7 elite and 7 sub-elite black belt taekwondo athletes performed eighteen RK, directed to two randomized height (9 to the head and 9 to the chest), with their dominant lower limb, combining maximum impact and speed, in a selective reaction time design. Angular and linear velocities of dominant leg and pelvis were recorded through 3D kinemetry. Ground reaction force parameters (GRF) were evaluated by force platform and surface electromyographic (sEMG) signals were recorded through wireless system from the Vastus Lateralis (VL), Biceps Femoris (BF), Rectus Femoris (RF), Tensor Fasciae Lata (TFL), Adductor Magnum (AM), Gluteus Maximum (GM), Gluteus Medium (Gmed) and Gastrocnemius Lateralis (GL) muscles of the kicking leg. EMGs data were rectified, filtered and normalized to the maximal value obtained for each muscle over all trials; cocontraction (CI) indexes of antagonist vs. overall (agonist and antagonist) activity were computed for hip abduction and hip and knee in flexion and extension. Premotor time of each muscle, reaction time and kicking time was assessed as well. Timing parameters and sEMG cocontraction index were significantly lower in elite group, while peak of linear (toe, ankle and knee), angular velocities (knee and hip), and GRF were significantly higher in elite than in sub-elite group. We conclude that reaction time, cocontraction, duration and velocity of kick could be useful in selecting top level taekwondo athletes and monitoring their training status